Medico-legal aspects of corneal refractive laser eye surgery. Issue 2 (April 2018) - Lake, Damian
It is estimated that over 40 million people have had laser vision correction worldwide since 1991. Laser-assisted subepithelial keratomileusis is commonplace in the UK in high street chains and from more bespoke suppliers. The standards around this treatment have always been regulated by the General Medical Council (GMC), but litigation cases have been common. The recent GMC guidance for cosmetic procedures and subsequent guidelines by the Royal College of Ophthalmologists cover advertising, facility regulations, equipment, consent and surgeon training which should improve industry practices and deliver improved patient safety standards.